Thermal-Hydraulic Characteristics of Helical Baffle Shell-and-Tube Heat Exchangers. Issue 13 (19th July 2020) - Abdelkader, Bassel A.; Jamil, Muhammad Ahmad; Zubair, Syed M.
Abstract: Shell-and-tube heat exchangers are frequently used in several industrial applications. A model was developed using engineering equations solver software to predict the performance of various baffle configurations of shell-and-tube heat exchangers. The model is based on the Bell-Delaware method for the segmental baffle, while mathematical correlations for the helical baffle are provided for design and analysis purpose. The accuracy of the present model is validated against the experimental data available in the literature. The results showed that helical baffles offer much higher performance compared to the segmental baffled heat exchanger. It was found that the performance of the helical baffle increases with increasing baffle angle until it reaches an optimum value; it then starts to decrease at an angle of 42°.